miR-125b and miR-223 Contribute to Inflammation by Targeting the Key Molecules of NFκB Pathway - Valmiki, Swati; Ahuja, Vineet; Puri, Niti; Paul, Jaishree (Frontiers in Medicine, 2020)
The contribution of miRNA in the pathogenesis of Ulcerative colitis (UC) has emerged in past few decades. Differential miRNA expression has been demonstrated in UC patients and their ability to target the genes involved in inflammatory pathway makes them suitable targets for the therapeutic interventions. MiR-125b and miR-223 have been demonstrated to get upregulated within the colonic mucosa of UC patients. Here, we explored the biological relevance of miR-125b and miR-223 altered expression during UC by identifying the potential gene targets for miR-125b and miR-223. TRAF6 and A20, the signaling molecules involved in NFκB pathway were identified as target genes for miR-125b while IKKα was identified as gene target for miR-223. The colonic mucosal samples from UC patients exhibited significant rise in miR-125b and miR-223 expression while a subsequent downregulation was observed in the expression of TRAF6, A20 and IKKα. Our in vitro findings revealed that miR-125b negatively regulates the expression of A20 and TRAF6 and an upregulated inflammatory response was generated in the absence of TRAF6 and A20. Similarly, miR-223 negatively regulated the expression of IKKα and resulted in higher p65 and pro-inflammatory cytokine expression. Our study highlights the contribution of miR-125b and miR-223 in the UC pathogenesis by suppressing the expression of TRAF6, A20 and IKKα. These two miRNAs could be considered as potential candidates for developing promising biomarkers for screening and diagnosis of UC.